Pendampingan Terhadap Pasangan Mental Retardation Dalam Mewujudkan Keluarga Sakinah Perspektif Teori Hierarki Kebutuhan Abraham Maslow - Fauziyah Putri Meilinda; Abbas Arfan; Supriyadi Supriyadi (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2022)
Conditions in the household life of a mentally retarded couple have various challenges, if there are a variety of problems in the life of a mentally retarded couple that cannot be handled properly, it will be a source of problems in the household. In the midst of these problems, there is the Sidoharjo village government which provides assistance through various efforts in finding a way out of various problems to create a sakinah family for mentally retarded couples. This study aims to analyze the assistance provided by the Sidoharjo Village Government to mentally retarded couples in realizing a sakinah family from the perspective of Abraham Maslow's hierarchy of needs theory. The results of this study indicate: 1) the perception of a sakinah family, a mental retardation partner, when under any circumstances they can still live life together, always have peace. 2) the problem faced by the Sidoharjo village government during the mentoring is communication. Problems faced by mental retardation couples are divided into two parts, namely internal and external. 3) the assistance provided by the Sidoharjo village government can be seen by fulfilling the five needs identified by Abraham Maslow, namely the fulfillment of financial needs that come from the assistance of various parties, assistance when there are family problems, assistance in terms of administrative arrangements, in terms of interaction providing understanding to the community. related to the condition of the partners with mental retardation.